Perencanaan Jangka Panjang di Perusahaan Multi Nasional - Situmorang, James Rianto (Jurnal Administrasi Bisnis, 2011)
Basically every company should use planning in corporate management becauseplanning is a management function which is considered more fundamental than theother functions such as organizing, leading and controlling. Planning is done to de-termine the objectives to be achieved in the future and the steps that must be done toachieve that goals. A company without good planning is impossible to achieve whatthe company wants in the future. One type of planning is a long-range planning orstrategic planning within a period of about 3-5 years. Multi national company (MNC)as a big company should have long-range planning to survive in the long term. Inaddition, the MNC which operates in many countries require long-range planningto be able to deal with various problems that exist in countries where the MNC hassubsidiary such as socio-cultural, political and economic factors.Keywords: planning, long-range planning, strategic planning, Multi NationalCompany